Active and Interactive Methods of Pedagogical Interaction in System of Distance Learning - T. A. Boronenko; A. V. Kaysina; V. S. Fedotova (Научный диалог)
The results of the analysis of the role of active and interactive methods of pedagogical interaction in distance learning systems are presented. The research urgency is caused by necessity of designing the content of educational programs of vocational training using distance learning technologies in the context of the activity paradigm of education, focused on improving its efficiency and quality. The authors identified pedagogical conditions of distance learning systems for the implementation of active and interactive teaching methods. The roles of participants in distance learning are characterized from the point of view of an active type of pedagogical interaction. The essence of the most common active and interactive methods of pedagogical interaction is considered, their advantages and disadvantages are determined. The necessity of a comprehensive range of active and interactive methods of pedagogical interaction to implement effective polylogical relationship of students at a distance with teachers and with each other is revealed. It is proved that an effective model of distance learning provides an active position of all participants of pedagogical interaction, as otherwise the distance learning takes the form of the traditional model of extramural studies and self-study of material, the student becomes an autonomous and isolated figure in the educational process. In this regard, special training of teachers for implementation of active and interactive methods in a distance learning system through refresher courses is required.